Implementation Of Uks Trias In Elemnetary School 22 Lubuk Minturun - Erita, Desnida; Putra, Randi Meidya; Rasyid, Willadi (Yayasan Sekora, 2018)
The problem in this research is that the implementation of the UKS TRIAS is not yet optimal in SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City. The purpose of this study was to describe the implementation of health education, health services, and a healthy school environment in SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City. This study used a descriptive type of research, namely to reveal and explain the implementation of UKS in SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City. The population in this study were all students in grade IV and V at SD Negeri 22 Lubuk Minturun, Koto Tangah District, Padang City, totaling 62 people. The sample technique used was a total sampling of 62 people. The data collection tool was a questionnaire using the Guttman scale model with the answer categories